HUBUNGAN PENDIDIKAN PELATIHAN, KETERAMPILAN DAN LINGKUNGAN KERJA DENGAN PRODUKTIVITAS KERJA PETUGAS REKAM MEDIS DI RUMAH SAKIT KELAS C TAHUN 2017 - Henny Maria Ulfa (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Productivity is how to produce or increase the results of goods and services as high aspossible with utilizing the resources in an efficient way.Several factors that affect productivitybut the education level of training, skill, and workplace. The purpose of this research is to findrelations education training, skill and workplace to productivity officers working medical recordin the hospital classC 2017.The population in this research is all medical recorder ofRSUDPetala Bumi Provinsi Riau dan RS Bina Kasih Pekanbarucity. There are24samplesof medicalrecorder in this reseach and taking by total sampling. Analysis the databy Fisher’s Exact.Theresults of the study there are the relationship between education training, skill and workplace toproductivity officers working medical record in the hospital class C.Keywords : Education and training , skill , working environment , productivity , the hospital